Analisis Sistem Informasi Akuntansi Penjualan Tunai sebagai Alat Pengendalian Internal pada PT Kim Putra Malang - Galuh Budi Astuti; Prodica Sarica (Akubis : Jurnal Akuntansi dan Bisnis, 2024)
The study aims to analyze the cash sales accounting information system as an internal control tool at PT Kim Putra Malang. This type of research is a case study using primary and secondary data. Data collection methods consist of field studies and literature studies using observation, interview, and documentation data collection techniques. The data analysis technique used is qualitative descriptive analysis. The problem faced by the company is the weakness of the cash sales accounting information system. This is proven by the occurrence of duplication in the administration and accounting sections as well as incomplete accounting documents and records in the company. The cause of this incident is the lack of human resources and the lack of understanding of the cash sales accounting information systems importance. As a result, errors occur when recording cash sales accounting and the company could experience losses. The results of the qualitative descriptive analysis are as follows. The company is advised to separate functions in the administration and accounting sections, improve the organizational structure, add warehouse cards, compile sales reports, and improve the cash sales system and procedures. The purpose of the suggestion above is internal control can be effectively executed.